Overcoming disembodiment: the effect of movement therapy on negative symptoms in schizophrenia, a multicenter randomized controlled Trial - Martin, Lily; Koch, Sabine C.; Hirjak, Dusan; Fuchs, Thomas (Frontiers in psychology, 2016)
Abstract Objective. Negative symptoms of patients with Schizophrenia are resistant to medical treatment or conventional group therapy. Understanding schizophrenia as a form of disembodiment of the self, a number of scientists have argued that the approach of embodiment and associated embodied therapies, such as Dance and Movement Therapy (DMT) or Body Psychotherapy (BPT), may be more suitable to explain the psychopathology underlying the mental illness and to address its symptoms. Hence the present randomized controlled trial (DRKS00009828, http://apps.who.int/trialsearch/) aimed to examine the effectiveness of manualized movement therapy (BPT/DMT) on the negative symptoms of patients with schizophrenia. Method. A total of 68 out-patients with a diagnosis of a schizophrenia spectrum disorder were randomly allocated to either the treatment (n = 44, 20 sessions of BPT/DMT) or the control condition (n = 24, treatment as usual (TAU)). Changes in negative symptom scores on the Scale for the Assessment of Negative Symptoms (SANS) were analyzed using Analysis of Covariance (ANCOVA) with Simpson-Angus Scale (SAS) scores as covariates in order to control for side effects of antipsychotic medication. Results. After twenty sessions of treatment (BPT/DMT or TAU), patients receiving movement therapy had significantly lower negative symptom scores (SANS total score, blunted affect, attention). Effect sizes were moderate and mean symptom reduction in the treatment group was 20.65%. Conclusion. The study demonstrates that embodied therapies, such as BPT/DMT, are highly effective in the treatment of patients with schizophrenia. Results strongly suggest that BPT/DMT should be embedded in the daily clinical routine.